HETEROGENITAS KUANTITAS DAN KUALITAS SEMEN SAPI BALI PEJANTAN DI UNIT PELAKSANA TEKNIS BALAI INSEMINASI BUATAN DAERAH BATURITI, TABANAN - N. M. P., Setyani; Sarini, N. P; Lanang Oka, I G. (Jurnal Peternakan Tropika; Vol 5 No 1 (2017), 2017)
This research was conducted to determine the heterogenity of quantity and quality of bali bull semen in Unit Pelaksana Teknis Balai Inseminasi Buatan Daerah ( UPT BIBD ) Baturiti, Tabanan from December 2016 until January 2017. Twelve Bali bulls in UPT BIBD Baturiti, Tabanan were used in this study. The variables observed in this study were macroscopic and microscopic characteristics of the semen. The data were analyzed using descriptive quantitative and qualitative analysis and coefficient of variationwere calculated for the quantitative data. The result of the study showed that the colour of Bali bull semen was milky cream, with the volume obtained per ejaculation was 4.8 ml up to 12.0 ml. In addition to that, the other macroscopic characteristics observed resulted in the pH between 6 to 7, spermatozoamotilitybetween 77.30 % until 97.79 %, the mass motions of Bali bull semen was ++ to +++. The last of microscopic characteristic observed was spermatozoa concentration vary between 1.078 x 10 9 /mland 2.118 x 10 9 /ml. The coefficient variation of the volume, concentration and motility of the spermatozoa were 23.98 %, 24.17 % and 7.67 % respectively. It can be concluded that quantity and quality of Bali bull semen was good. Although that volume and concentration of semen were vary, but their spermmotility was uniform. Overall, it can be said that Bali bull semen in UPT BIBD Baturiti was heterogen and was good in sperm quality chatagorize and the most superior Bali bull in UPT BIBD Baturiti, Tabanan was Buwana Merta. Normal 0 false false false IN X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:8.0pt; mso-para-margin-left:0cm; line-height:107%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;}
Keywords: heterogenity, quantity and quality, bali cattle, BIBD Baturiti